# College AlgebraAnswers 3Bids 1Other questions 10

College AlgebraAnswers 3Bids 1Other questions 10.

Hello,The current answers are incorrect and I need the corrected answers. Thanks, 1. Solve the following system of equations using matrices. Use Gaussian elimination with back substitution or Gauss-Jordan elimination.x – 2y + z = 0  y – 3z = -1  2y + 5z = -2   [removed] A. {(-1, -2, 0)} [removed] B. {(-2, -1, 0)} [removed] C. {(-5, -3, 0)} [removed] D. {(-3, 0, 0)}  2. Solve the following system of equations using matrices. Use Gaussian elimination with back substitution or Gauss-Jordan elimination. 2x – y – z = 4  x + y – 5z = -4  x – 2y = 4   [removed] A. {(2, -1, 1)} [removed] B. {(-2, -3, 0)} [removed] C. {(3, -1, 2)} [removed] D. {(3, -1, 0)}      3. Find the products AB and BA to determine whether B is the multiplicative inverse of A. A =0 0 11 0   00 1   0 B =0 1 00 0   11 0   0   [removed] A. AB = I; BA = I3; B = A [removed] B. AB = I3; BA = I3; B = A-1 [removed] C. AB = I; AB = I3; B = A-1 [removed] D. AB = I3; BA = I3; A = B-1  4. Use Cramer’s Rule to solve the following system.2x = 3y + 2  5x = 51 – 4y   [removed] A. {(8, 2)} [removed] B. {(3, -4)} [removed] C. {(2, 5)} [removed] D. {(7, 4)} 5. Use Gaussian elimination to find the complete solution to the following system of equations, or show that none exists. 2w + x – y = 3  w – 3x + 2y = -4  3w + x – 3y + z = 1  w + 2x – 4y – z = -2   [removed] A. {(1, 3, 2, 1)} [removed] B. {(1, 4, 3, -1)} [removed] C. {(1, 5, 1, 1)} [removed] D. {(-1, 2, -2, 1)}    6. Solve the following system of equations using matrices. Use Gaussian elimination with back substitution or Gauss-Jordan elimination. x + 2y = z – 1  x = 4 + y – z  x + y – 3z = -2   [removed] A. {(3, -1, 0)} [removed] B. {(2, -1, 0)} [removed] C. {(3, -2, 1)} [removed] D. {(2, -1, 1)}  7. Use Gauss-Jordan elimination to solve the system.-x – y – z = 1  4x + 5y = 0  y – 3z = 0   [removed] A. {(14, -10, -3)} [removed] B. {(10, -2, -6)} [removed] C. {(15, -12, -4)} [removed] D. {(11, -13, -4)}  8. Use Gaussian elimination to find the complete solution to the following system of equations, or show that none exists. w – 2x – y – 3z = -9  w + x – y = 0  3w + 4x + z = 6  2x – 2y + z = 3   [removed] A. {(-1, 2, 1, 1)} [removed] B. {(-2, 2, 0, 1)} [removed] C. {(0, 1, 1, 3)} [removed] D. {(-1, 2, 1, 1)}  9. Use Gaussian elimination to find the complete solution to the following system of equations, or show that none exists. 8x + 5y + 11z = 30  -x – 4y + 2z = 3  2x – y + 5z = 12   [removed] A. {(3 – 3t, 2 + t, t)} [removed] B. {(6 – 3t, 2 + t, t)} [removed] C. {(5 – 2t, -2 + t, t)} [removed] D. {(2 – 1t, -4 + t, t)}  10. Solve the following system of equations using matrices. Use Gaussian elimination with back substitution or Gauss-Jordan elimination. x + y + z = 4  x – y – z = 0  x – y + z = 2   [removed] A. {(3, 1, 0)} [removed] B. {(2, 1, 1)} [removed] C. {(4, 2, 1)} [removed] D. {(2, 1, 0)}  11. Use Cramer’s Rule to solve the following system.  x + y = 7  x – y = 3   [removed] A. {(7, 2)} [removed] B. {(8, -2)} [removed] C. {(5, 2)} [removed] D. {(9, 3)}  12. Solve the following system of equations using matrices. Use Gaussian elimination with back substitution or Gauss-Jordan elimination.  3×1 + 5×2 – 8×3 + 5×4 = -8  x1 + 2×2 – 3×3 + x4 = -7  2×1 + 3×2 – 7×3 + 3×4 = -11  4×1 + 8×2 – 10×3+ 7×4 = -10   [removed] A. {(1, -5, 3, 4)} [removed] B. {(2, -1, 3, 5)} [removed] C. {(1, 2, 3, 3)} [removed] D. {(2, -2, 3, 4)}  13. Use Cramer’s Rule to solve the following system.  4x – 5y = 17  2x + 3y = 3   [removed] A. {(3, -1)} [removed] B. {(2, -1)} [removed] C. {(3, -7)} [removed] D. {(2, 0)}  14. Use Gaussian elimination to find the complete solution to each system.x – 3y + z = 1  -2x + y + 3z = -7  x – 4y + 2z = 0   [removed] A. {(2t + 4, t + 1, t)} [removed] B. {(2t + 5, t + 2, t)} [removed] C. {(1t + 3, t + 2, t)} [removed] D. {(3t + 3, t + 1, t)}  15. Use Gaussian elimination to find the complete solution to the following system of equations, or show that none exists. 5x + 8y – 6z = 14  3x + 4y – 2z = 8  x + 2y – 2z = 3   [removed] A. {(-4t + 2, 2t + 1/2, t)} [removed] B. {(-3t + 1, 5t + 1/3, t)} [removed] C. {(2t + -2, t + 1/2, t)} [removed] D. {(-2t + 2, 2t + 1/2, t)}  16. Solve the system using the inverse that is given for the coefficient matrix.2x + 6y + 6z = 8 2x + 7y + 6z =10 2x + 7y + 7z = 9 The inverse of:2 2 2  6 7 7  6 6 7 is7/2 -1 0  0 1 -1  -3 0 1   [removed] A. {(1, 2, -1)} [removed] B. {(2, 1, -1)} [removed] C. {(1, 2, 0)} [removed] D. {(1, 3, -1)}  17. Use Cramer’s Rule to solve the following system.4x – 5y – 6z = -1  x – 2y – 5z = -12  2x – y = 7   [removed] A. {(2, -3, 4)} [removed] B. {(5, -7, 4)} [removed] C. {(3, -3, 3)} [removed] D. {(1, -3, 5)}  18. Find the solution set for each system by finding points of intersection.x2 + y2 = 1  x2 + 9y = 9   [removed] A. {(0, -2), (0, 4)} [removed] B. {(0, -2), (0, 1)} [removed] C. {(0, -3), (0, 1)} [removed] D. {(0, -1), (0, 1)}   19. Find the standard form of the equation of the ellipse satisfying the given conditions. Endpoints of major axis: (7, 9) and (7, 3)  Endpoints of minor axis: (5, 6) and (9, 6)  [removed] A. (x – 7)2/6 + (y – 6)2/7 = 1 [removed] B. (x – 7)2/5 + (y – 6)2/6 = 1 [removed] C. (x – 7)2/4 + (y – 6)2/9 = 1 [removed] D. (x – 5)2/4 + (y – 4)2/9 = 1   20. Find the vertex, focus, and directrix of each parabola with the given equation. (x + 1)2 = -8(y + 1)  [removed] A. Vertex: (-1, -2); focus: (-1, -2); directrix: y = 1 [removed] B. Vertex: (-1, -1); focus: (-1, -3); directrix: y = 1 [removed] C. Vertex: (-3, -1); focus: (-2, -3); directrix: y = 1 [removed] D. Vertex: (-4, -1); focus: (-2, -3); directrix: y = 1  21. Find the vertex, focus, and directrix of each parabola with the given equation. (x + 1)2 = -8(y + 1)  [removed] A. Vertex: (-1, -2); focus: (-1, -2); directrix: y = 1 [removed] B. Vertex: (-1, -1); focus: (-1, -3); directrix: y = 1 [removed] C. Vertex: (-3, -1); focus: (-2, -3); directrix: y = 1 [removed] D. Vertex: (-4, -1); focus: (-2, -3); directrix: y = 1  22. Find the standard form of the equation of each hyperbola satisfying the given conditions. Foci: (-4, 0), (4, 0) Vertices: (-3, 0), (3, 0)  [removed] A. x2/4 – y2/6 = 1 [removed] B. x2/6 – y2/7 = 1 [removed] C. x2/6 – y2/7 = 1 [removed] D. x2/9 – y2/7 = 1  23. Locate the foci of the ellipse of the following equation. x2/16 + y2/4 = 1  [removed] A. Foci at (-2√3, 0) and (2√3, 0) [removed] B. Foci at (5√3, 0) and (2√3, 0) [removed] C. Foci at (-2√3, 0) and (5√3, 0) [removed] D. Foci at (-7√2, 0) and (5√2, 0)  24. Locate the foci and find the equations of the asymptotes.   x2/9 – y2/25 = 1  [removed] A. Foci: ({±√36, 0) ;asymptotes: y = ±5/3x [removed] B. Foci: ({±√38, 0) ;asymptotes: y = ±5/3x [removed] C. Foci: ({±√34, 0) ;asymptotes: y = ±5/3x [removed] D. Foci: ({±√54, 0) ;asymptotes: y = ±6/3x  25. Find the standard form of the equation of each hyperbola satisfying the given conditions. Foci: (0, -3), (0, 3) Vertices: (0, -1), (0, 1)  [removed] A. y2 – x2/4 = 0 [removed] B. y2 – x2/8 = 1 [removed] C. y2 – x2/3 = 1 [removed] D. y2 – x2/2 = 0  26. Convert each equation to standard form by completing the square on x and y. 4×2 + y2 + 16x – 6y – 39 = 0  [removed] A. (x + 2)2/4 + (y – 3)2/39 = 1 [removed] B. (x + 2)2/39 + (y
&
#8211; 4)2/64 = 1 [removed] C. (x + 2)2/16 + (y – 3)2/64 = 1 [removed] D. (x + 2)2/6 + (y – 3)2/4 = 1  27. Find the standard form of the equation of the following ellipse satisfying the given conditions.  Foci: (-5, 0), (5, 0) Vertices: (-8, 0), (8, 0)  [removed] A. x2/49 + y2/ 25 = 1 [removed] B. x2/64 + y2/39 = 1 [removed] C. x2/56 + y2/29 = 1 [removed] D. x2/36 + y2/27 = 1  28. Find the focus and directrix of each parabola with the given equation. x2 = -4y  [removed] A. Focus: (0, -1), directrix: y = 1 [removed] B. Focus: (0, -2), directrix: y = 1 [removed] C. Focus: (0, -4), directrix: y = 1 [removed] D. Focus: (0, -1), directrix: y = 2  29. Find the vertex, focus, and directrix of each parabola with the given equation. (y + 1)2 = -8x  [removed] A. Vertex: (0, -1); focus: (-2, -1); directrix: x = 2 [removed] B. Vertex: (0, -1); focus: (-3, -1); directrix: x = 3 [removed] C. Vertex: (0, -1); focus: (2, -1); directrix: x = 1 [removed] D. Vertex: (0, -3); focus: (-2, -1); directr

The post College AlgebraAnswers 3Bids 1Other questions 10 appeared first on homeworkhandlers.com.

College AlgebraAnswers 3Bids 1Other questions 10

## Why US?

##### 100% Confidentiality

Information about customers is confidential and never disclosed to third parties.

##### Timely Delivery

No missed deadlines – 97% of assignments are completed in time.

##### Original Writing

We complete all papers from scratch. You can get a plagiarism report.

##### Money Back

If you are convinced that our writer has not followed your requirements, feel free to ask for a refund.